(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2019)
That the building of the national economy depends on the extent of the possibility of transition from the rent economy seeking to increase GDP (GDP1), and the tendency to manage projects with external sources of funding, or allow projects with foreign capital is a necessity. The strategic challenges faced by the economy in countries that have experience in investment projects have faced several factors internal and external for a period of time and not a few and the pressures and difficulties and failures have affected in one way or another on the development work in that country. On this basis, the stakeholders have a role to pay attention to the issue of the feasibility of the pattern of foreign investment in the investment environment in general, so that industrial or service investment projects can contribute to the economic development of that country. The research aims at shedding light on the differentiation between investment projects of different types. "The researcher assumed that the pattern of long-term green investment is feasible within the investment environment, and brown investment is useless to the weakness of the family through investment years within the same investment environment. The researcher used comparative tools and measures such as net present value, self-financing ability, rate of return on investment and repayment period of invested capital. The researcher reached a number of conclusions, including that the strengthening of the competitiveness of foreign projects in Iraq depends on laws that legislate and encourage foreign investment for investment. The study showed that the investment pattern in the practical aspect is that the long-term green investment is economically feasible within the Iraqi investment environment, while the brown investment showed the economic inefficiency of the weakness of the family through investment years. The investment pattern also offers wider opportunities to encourage the investor to invest with the various sectors of development Investment.